Psychologization and the subject of late modernity - De Vos, Jan 1967- (Palgrave Macmillan, 2013)
"If you want to know something about man, don't study the human, don't study psychology, study psychologization...Jan De Vos starts where other critiques on psychology end, putting forward a breathtaking simple but most revealing argument: psychology is psychologization.This fresh and pioneering approach asks what it means to become the psychologist of one's own life. If something is not working in our education, in our marriage, in our work and in society in general we turn to the psy-sciences. But is the latter's paradigm precisely not relying on feeding psychological theories into the field of research and action?Jan De Vos traces psychologization back to the Enlightenment and then proceeds to late-modernity. Engaging with seminal thinkers such as La Mettrie, Husserl, Lasch and Agamben, he meanwhile teases out the possibilities and the limits of using psychoanalytic theory as a critical tool.Whatever level of expertise they possess, readers working in or simply interested in psychology, social psychology or cultural studies will find something of value here. If you have once felt some uneasiness or discontent in current psychologized culture, this book offers challenging and thought-provoking insights"..